The Effect of Service Quality, Management Information System and Passport Administration Rates on Public Satisfaction with Education as an Intervening Variable in the Task Area of Class II Immigration Office Tanjung Balai Karimun - KHAIDIR, Khaidir; CATRAYASA, I Wayan; NGALIMAN, Ngaliman (PT Keberlanjutan Strategis Indonesia, 2024)
Information was found regarding complaints regarding slow operational access to online services, tariff provisions that must be paid, and not having received education about M-Paspor, Eazy and other online systems. This research using a quantitative approach concludes that service quality, passport processing fees and public education have a significant direct influence on public satisfaction. Meanwhile, the management information system has no significant direct effect on public satisfaction and service quality has no significant direct effect on public education. Then the management information system and passport processing fees have a significant direct influence on public education. Furthermore, public education is not able to intervene in the influence of service quality and management information systems on public satisfaction, but public education is able to intervene in the influence of passport processing fees on public satisfaction as a partial mediation (intervening) variable. It is recommended to the Head of the Class II Tanjung Balai Karimun Immigration Office to: optimize the implementation of education to the public regarding the service system and tariffs and strive to improve the quality of service, the effectiveness of implementing the management information system related to passport processing.